2013
DOI: 10.1002/eji.201343782
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal innate immune cells regulate both gut homeostasis and intestinal inflammation

Abstract: Continuous exposure of intestinal mucosal surfaces to diverse microorganisms and their metabolites reflects the biological necessity for a multifaceted, integrated epithelial and immune cell-mediated regulatory system. The development and function of the host cells responsible for the barrier function of the intestinal surface (e.g., M cells, Paneth cells, goblet cells, and columnar epithelial cells) are strictly regulated through both positive and negative stimulation by the luminal microbiota. Stimulation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
92
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 57 publications
(122 reference statements)
3
92
0
2
Order By: Relevance
“…Their localization in the follicles-associated epithelia of Payer's patches and/or isolated lymphoid follicles facilitates the induction of antigen-specific immune response within the mucous membrane. The last study showed that M cells are the entry point for intra-tissues commensal flora inducing IgA production in Peyer's patches [5,7]. The last equally important cells from epithelial layer are columnar epithelial cells forming very tight monolayer surface barrier, being regulated by the commensal microbiota.…”
Section: The Role Of Microbiotamentioning
confidence: 99%
See 4 more Smart Citations
“…Their localization in the follicles-associated epithelia of Payer's patches and/or isolated lymphoid follicles facilitates the induction of antigen-specific immune response within the mucous membrane. The last study showed that M cells are the entry point for intra-tissues commensal flora inducing IgA production in Peyer's patches [5,7]. The last equally important cells from epithelial layer are columnar epithelial cells forming very tight monolayer surface barrier, being regulated by the commensal microbiota.…”
Section: The Role Of Microbiotamentioning
confidence: 99%
“…NLRs are the group of intra-cellular pattern recognitions receptors (PRRs) involved in the recognition of many DAMPs and PAPMs (danger and pathogen-associated molecular patterns) in commensal and pathogenic microbiota. Inflammasome is a crucial structure for defence to pathogens but, from the other perspective, is involved in pathogenesis of autoinflammatory and autoimmune diseases following the prolonged inflammatory process [4][5][6]. The forming of inflammasome is not the only way of interaction between microbiota and immune systems.…”
Section: The Role Of Microbiotamentioning
confidence: 99%
See 3 more Smart Citations